Choosing the right path: membrane trafficking and infectious entry of small DNA tumor viruses. (August 2019) - Bugnon Valdano, Marina; Pim, David; Banks, Lawrence
Abstract : To infect mammalian cells, all infectious viruses must cross a common set of biophysical membrane barriers to gain access to the cell. The virus capsid proteins attach to a host cell, become endocytosed, and traffic the viral genome to sites of replication. To do this they must interact with the membrane-confined organelles that control endocytosis, endosomal sorting, processing, and degradation of biological molecules. In this review, we highlight some recent advances in our understanding of the mechanisms that small non-enveloped DNA tumor viruses, such as Human Papillomavirus (HPV) and Polyomaviruses (PyV) employ to attain infectious entry. These viruses exploit different pathways to mediate entry, uncoating and subsequent transport to the nucleus via the Trans Golgi Network (TGN) or the Endoplasmic Reticulum (ER). Understanding how the viral capsid proteins interact with cellular membranous organelles sheds light on the novel ways by which viruses can hi-jack endocytic transport pathways and provides unique insights into how the highly complex machinery controlling cargo fate determination is regulated within the cell.